ANALISIS PENGARUH VARIABEL STORE ATMOSPHERE (SUASANA TOKO) TERHADAP MINAT BELI ULANG PADA KOPI MERAPI - Muhammad Candra Saputra; Sukardi Sukardi (Jurnal Fokus Manajemen Bisnis, 2018)
This paper aims to identify the effect of the atmosphere on consumer repurchase intentions at Yogyakarta's Merapi Coffee. The sample consisted of 80 respondents who usually visited Merapi Coffee Shop. Data is collected through a well structured questionnaire. This research is a quantitative study. Sampling with purposive sampling. Data collection in this study uses a questionnaire that will be tested for validity and reliability, for data analysis using multiple regression analysis, f test, t test, and R square. The subjects of this research are Yogyakarta Merapi Coffee consumers. The results of the t test show that: 1) Cleanliness significantly influences the repurchase interest in Merapi coffee with sig. 003 <0.05.2) Music has no significant effect on repurchase interest in Merapi coffee with a value of sig.0,846> 0.05.3) Aroma has no significant effect on repurchase interest in Merapi coffee with a sig value. 0,157> 0,05.4) Temperature has a significant effect on repurchase interest in Merapi coffee with sig. 000 <0.05.5) Lighting has no significant effect on repurchase interest in Merapi coffee with sig. 0.097> 0.05.6) Color has no significant effect on repurchase interest in Merapi coffee with a value of sig.0,146> 0.05.7) Display has a significant effect on repurchase interest in Merapi coffee with a sig value. 0.001 <0.05.